The origins of tolerant and repressive secularism: an analysis of the United States and France in comparative perspectives - Atsü, E (2021)
In the field of political science, the term “secularism” is commonly understood as a statecraft doctrine that guarantees the separation between religion and state. A careful examination of history discloses that the United States and France are the two founding nations of this principle. Notwithstanding their common foundation of secularism, these two countries exhibit substantive variation in the implementation of this constitutional tenet — notably, in the extent to which they tolerate religious freedom and its expression. My thesis investigates the causal factors as to why the United States practices a tolerant form of secularism, which guarantees freedom of religion; while France exercises a repressive type of secularism, which is concerned with freedom from religion. For this purpose, my research project relies upon a qualitative analysis using comparative–historical methods and within-case process tracing. In essence, I argue that the outcome of the political conflict that occurred between liberal and conservative elites during the periods of secular state-building explains the type of secularism adopted by the country and its persistence in the mid-long run. After providing in-depth and theory-guided narratives of the American and French cases, I explore the external validity of my argument on two shadow cases, namely Senegal and pre-AKP Turkey. These brief studies echo the findings from my main cases by showing that the adaptation and persistence of tolerant secularism in Senegal is the result of a political comprise reached between liberals and conservatives during the country’s process of secular state-building similar to the United States; whereas liberals’ political victory over conservatives in Turkey during a comparable episode resulted in the imposition and persistence of repressive secularism like in France, until the AKP leadership managed to halt it.